Impact of Abstinence and of Reducing Illicit Drug Use Without Abstinence on Human Immunodeficiency Virus Viral Load. (17th April 2019) - Nance, Robin M; Trejo, Maria Esther Perez; Whitney, Bridget M; Delaney, Joseph A C; Altice, Fredrick L; Beckwith, Curt G; Chander, Geetanjali; Chandler, Redonna; Christopoulous, Katerina; Cunningham, Chinazo; Cunningham, William E; Del Rio, Carlos; et al.
Abstract: Background: Substance use is common among people living with human immunodeficiency virus (PLWH) and a barrier to achieving viral suppression. Among PLWH who report illicit drug use, we evaluated associations between HIV viral load (VL) and reduced use of illicit opioids, methamphetamine/crystal, cocaine/crack, and marijuana, regardless of whether or not abstinence was achieved. Methods: This was a longitudinal cohort study of PLWH from 7 HIV clinics or 4 clinical studies. We used joint longitudinal and survival models to examine the impact of decreasing drug use and of abstinence for each drug on viral suppression. We repeated analyses using linear mixed models to examine associations between change in frequency of drug use and VL. Results: The number of PLWH who were using each drug at baseline ranged from n = 568 (illicit opioids) to n = 4272 (marijuana). Abstinence was associated with higher odds of viral suppression (odds ratio [OR], 1.4–2.2) and lower relative VL (ranging from 21% to 42% by drug) for all 4 drug categories. Reducing frequency of illicit opioid or methamphetamine/crystal use without abstinence was associated with VL suppression (OR, 2.2, 1.6, respectively). Reducing frequency of illicit opioid or methamphetamine/crystal use without abstinence was associated with lower relative VL (47%, 38%, respectively). Conclusions: Abstinence was associated with viral suppression. In addition, reducing use of illicit opioids or methamphetamine/crystal, even without abstinence, was also associated with viral suppression. Our findings highlight the impact of reducing substance use, even when abstinence is not achieved, and the potential benefits of medications, behavioral interventions, and harm-reduction interventions. Abstract : We examined the longitudinal associations between reducing illicit drug use frequency and human immunodeficiency virus viral load. Abstinence for all drugs was associated with viral suppression. Reducing frequency of illicit opioid or methamphetamine/crystal use without abstinence was also associated with viral suppression, which has policy implications for harm-reduction substance use interventions that successfully reduce use even when abstinence is not achieved.